Priority approach as an effective tool for managing social development of personnel in the context of social management in enterprises - Chupyr, Olena; Kalinichenko, Liudmyla; Ustilovska, Anastasiya (International Journal of Engineering and Technology, 2018)
To ensure a stable, highly efficient operation of enterprises, it is necessary to create a scientifically based system for managing all aspects of their activities, in particular, pay special attention to the planning of social processes. The essence of social management determines its formation and functioning as a system. In order to avoid scattering of the funds allocated for social development of personnel, it is necessary to determine the primary social objectives and appropriate funds for their implementation. In this regard, a model of a scientifically based system for planning social development of personnel has been proposed, using a priority approach to social management based on assessing the level of social development of personnel, which will help focus on the objectives that are most important for the enterprise and concentrate financial resources in the most important areas of its social development. It is necessary to plan the expenses for social development of the enterprise with a real consideration for the opinions of the personnel, which is possible through defining the social priorities by the quantitative method on the basis of processing the results of a survey of employees.Â Â